Role of the Family Nurse with patients with Down Syndrome (Research, Society and Development, 2024)
Objective: To identify in the literature the actions disseminated by the family nurse regarding the family of patients with Down syndrome. Methodology: A exploratory bibliographic review research was carried out, using a qualitative approach. The data collection took place from August to November 2023 with publications between the years 2019 and 2024, using virtual databases and meeting the analysis criteria, and it was possible to build a flowchart on the process of selecting the articles, following the search strategies and inclusion of the descriptors, totaling 11 articles after filtering. Results were carried out through 3 categories: The social construction of Down Syndrome in the XXI century, The role of the family nurse in the management of Down syndrome and the family-centered care of the individual with Down syndrome. It is concluded that the work context signals that nurses need to be prepared to disseminate their work, always trained, in order to achieve homogeneous management, since they are patients with Down Syndrome.